The role of Virus "X" (Tortoise Picornavirus) in kidney disease and shell weakness syndrome in European tortoise species determined by experimental infection - Paries, Susanne; Funcke, Svenja; Kershaw, Olivia; Failing, Klaus; Lierz, Michael; Justus Liebig University Giessen (My University, 2019)
Tortoise Picornavirus (ToPV) commonly known as Virus "X" was recently discovered in juvenile European tortoises suffering from soft carapace and plastron as well as kidney disease. Therefore, this virus was a potential candidate to be a causative agent for these disease patterns. Spur thighed tortoises (Testudo graeca) seemed to be more susceptible to establish clinical symptoms than other European species like T. hermanni. Thus this trial investigated the role of ToPV in the described syndrome. Two groups of juvenile European tortoises (T. graeca and T.hermanni) each of 10 animals, were cloacally, oronasally and intracoelomically inoculated with an infectious dose (~ 2000 TICD) of a ToPV strain isolated from a diseased T. graeca. A control group of two animals of each species received non-infected cell culture supernatant. The tortoises were examined daily and pharyngeal and cloacal swabs for detection of ToPV-RNA by RT-PCR were taken from each animal every six days for a period of 6 months. At the end of the study the remaining animals were euthanised and dissected. Bacteriological and parasitological tests were performed and organ samples of all tortoises were investigated by RT-PCR for the presence of ToPV and histopathology. Animals that were euthanised at the end of the experiment, were examined for presence of specific anti-ToPV antibodies. Several animals in both inoculated groups showed retarded growth and a light shell weakness, in comparison to the control animals. Three animals were euthanised during the trial, showing reduced weight gain, retarded growth, severe shell weakness and apathy, in parallel to clinical observations in naturally infected animals. In all inoculated animals of both species an intermittent virus shedding, starting from 18 days post inoculation (d.p.i.), till 164 d.p.i. was detected, while the control animals remained negative. The virus was successfully reisolated in terrapene heart cell culture in 16 of 20 inoculated animals of both species. Histopathology of most inoculated animals revealed a lack of bone remodeling and vacuolisation in kidney tubuli which supports the described pathogenesis of nephropathy and osteodystrophy. Anti- ToPV antibody titres ranged from 1:2 to greater than 1:256 in 13 of 20 animals, whereas all control animals were seronegative. The study proofed the Henle Kochs postulates of ToPV as causative agent for shell dystrophy and kidney disease in both testudo species. The proposed species specific sensitivity towards clinical disease was not observed.
Keywords: ddc:630